Determinant of Sukuk Market Development - M. Thoha Ainun Najib; Silky Roudhotus Sa’adah (Universitas Nusantara PGRI Kediri, 2025)
The research covers the significant phenomenon of sukuk in the global economy post-crisis. It has proven index growth against conventional securities. There is still a literature gap regarding the effect of institutional quality on Islamic financial markets, bringing sukuk into the picture despite enjoying progressive growth in Sukuk. Therefore, the research aims to empirically investigate the influence of macroeconomics and institutional quality on the sukuk market development based on secondary data from WDI, ICRG, and IIFM. The study objects thus include the top five sukuk-issuing countries from 2008 to 2023: Malaysia, U.A.E., Saudi Arabia, Indonesia, and Bahrain-but analyzed with the aid of dynamic panel data regression. Results indicate that GDP per capita, exchange rate, and indicators of institutional quality significantly and positively influence the sukuk market, while inflation and corruption control have significant negative impacts; hence, this research underscores the requirement of macroeconomic stability and better institutional quality for better development of the Islamic capital market.